Kolaborasi Model Triple Helix Dalam Peningkatan Luasan Hutan Melalui Metode Agroforestry Berbasis Partisipasi Desa - Azwan Rifa'i; Suherry Suherry; Alfi Husni; Desmayeti Arfa; Fatma Pratiwi (STISIPOL Raja Haji, 2026)
As a country endowed with abundant tropical forest resources, Indonesia has a strategic interest in preserving environmental sustainability through participatory and sustainable forest management. However, efforts to increase forest coverage continue to face various structural challenges, including high rates of deforestation, land degradation, and weak collaborative governance among stakeholders. Many forest management programs, including agroforestry initiatives, tend to be implemented in a sectoral manner and have not fully positioned rural communities as strategic actors in decision-making processes. In this context, the application of the Triple Helix collaborative model involving government, academia, and the private sector represents a relevant approach to fostering innovation in forest management. The main issue examined in this study is the absence of a wellformulated Triple Helix collaboration model that places villages at the center of governance in agroforestry development. This study aims to analyze how the design of collaboration among actors within the Triple Helix framework can enhance forest expansion through a village-based participatory agroforestry approach. The research employs a qualitative method through a literature review of academic sources, government policies, and previous studies. The findings indicate that Triple Helix collaboration can strengthen forest governance by integrating scientific knowledge, development policies, and the local wisdom of rural communities. This approach not only contributes to the expansion of forest areas but also enhances rural economic welfare and ecological resilience in a sustainable manner.